The Relationship Between Knowledge And Attitudes Of Mothers About Premenopause In Silau Paribuan Village Silau Kahean District - Nurianti, Irma (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Premenopause is something that is very worried and feared by every mother. Changes that occur during the premenopause period will lead to decreased estrogen hormone production accompanied by psychological and physical complaints, which are characterized by irregular menstrual cycles with prolonged menstrual bleeding and large bleeding sizes accompanied by pain. This study aims to determine the relationship between knowledge and attitudes of mothers about pre menopause. This type of research is analytic with a cross sectional design in this study a population of 60 premenopausal women. The sample of this study was 38 people with purvosive sampling technique. The results showed that there was a relationship between knowledge and attitudes of mothers about premenopause (p = 0.00). Mother's knowledge in dealing with premenopause is lacking and mother's attitude in dealing with premenopause is positive. Mother's knowledge is lacking because the mother has never received information about premenopause and has never received health education about premenopause. A positive mother's attitude is caused because the mother is able to divert unpleasant feelings into positive things by doing various activities, and assumes that what is experienced during premenopause is a natural thing that will be experienced by every mother. It is hoped that health workers will provide health education about premenopause, and premenopausal mothers are expected to be proactive in seeking information related to premenopause.